Abnormal movements in first-episode, nonaffective psychosis: Dyskinesias, stereotypies, and catatonic-like signs. Issue 1 (30th March 2015) - Compton, Michael T.; Fantes, Francisco; Wan, Claire Ramsay; Johnson, Stephanie; Walker, Elaine F.
Abstract: Motor abnormalities represent a neurobehavioral domain of signs intrinsic to schizophrenia-spectrum disorders, though they are commonly attributed to medication side effects and remain understudied. Individuals with first-episode psychosis represent an ideal group to study innate movement disorders due to minimal prior antipsychotic exposure. We measured dyskinesias, stereotypies, and catatonic-like signs and examined their associations with: (1) age at onset of psychotic symptoms and duration of untreated psychosis; (2) positive, negative, and disorganized symptoms; (3) neurocognition; and (4) neurological soft signs. Among 47 predominantly African American first-episode psychosis patients in a public-sector hospital, the presence and severity of dyskinesias, stereotypies, and catatonic-like features were assessed using approximately 30-min video recordings. Movement abnormalities were rated utilizing three scales (Dyskinesia Identification System Condensed User Scale, Stereotypy Checklist, and Catatonia Rating Scale). Correlational analyses were conducted. Scores for each of three movement abnormality types were modestly inter-correlated ( r =0.29–0.40). Stereotypy score was significantly associated with age at onset of psychotic symptoms ( r =0.32) and positive symptom severity scores ( r =0.29–0.41). There were no meaningful or consistent associations with negative symptom severity, neurocognition, or neurological soft signs. Abnormal movements appear to represent a relatively distinct phenotypic domain deserving of further research.